Strategic Triangle Penguatan Program Keluarga Harapan (PKH Plus) di Kecamatan Driyorejo Kabupaten Gresik - Evianti Kharima; Diana Hertati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the strategic triangle of strengthening the Family Hope Program (PKH Plus) in Driyorejo District, Gresik Regency. PKH Plus is important as part of social protection for the elderly, especially amidst the economic and social challenges they face. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The analysis is based on the strategic triangle model (Moore, 1995) which consists of public value, legitimacy and environmental support, and operational capacity. The results of the study indicate that PKH Plus has a direct impact on improving the quality of life of the elderly in Driyorejo District, Gresik Regency, both in terms of meeting basic needs, access to services, and feeling cared for. Support from various parties as well as the availability of adequate human resources and facilities further strengthens the implementation of the program.  This study concludes that the strengthening strategy of PKH Plus in Driyorejo District, Gresik Regency has been implemented well and has a real impact on the welfare of the elderly. Institutional synergy and improving the quality of implementers are important to ensure the sustainability of the program.